Explicit homogenized equation of a boundary-value problem in two-dimensional domains separated by an interface highly oscillating between two concentric ellipses - Vinh, P.C.; Tung, D.X. (Archives of Mechanics, 2012)
The main purpose of this paper is to find the homogenized equation and the associate continuity condition in the explicit form of a boundary-value problem in two-dimensional domains separated by an interface oscillating rapidly between two concentric ellipses. This boundary-value problem originates from various mechanical problems. By the homogenization method and following the techniques presented recently by these authors the homogenized equation and the associate continuity condition in the explicit form are derived. Since the obtained homogenized equation is totally explicit it is convenient to use.